Electrodeposition Cu and roll transfer of graphene for large scale fabrication of Cu-graphene nanolayered composite. (23rd September 2019) - Kim, Sang-Min; Kim, Wonsik; Hwangbo, Yun; Kim, Jae-Hyun; Han, Seung Min
Abstract: Nanolayered composites are reported to exhibit high strength due to the high density of interfaces. Previously, metal-graphene nanolayered composite had been fabricated by vacuum based deposition of metal layers and wet transfer of graphene layers, both of which are time consuming processes that limit the scalability of the nanolayered composite. In this study, the vacuum based deposition of metal and wet transfer of graphene have been replaced with electrodeposition of metal and roll-based dry transfer of graphene to greatly enhance the scalability of the nanolayered composite fabrication. Fabricated Cu-graphene nanolayered composites with layer spacing of 200 nm, 300 nm, and 400 nm were tested under compression, and the strengths are calculated to be 1.38 GPa, 1.15 GPa, and 1.06 GPa, respectively. The strengths are within the range reported previously for the case of wet transfer and sputter deposited metal, but the new fabrication method has greatly enhanced scalability.